Is It My Job to Make Him Care? Middle‐Class Women and Gender Inequality in Ho Chi Minh City. (28th October 2015) - Higgins, Rylan
Abstract: Despite considerable material and social gains, urban middle‐class women in turn of the 21st century Vietnam continued to face gender inequality. Although the nature of gender inequality had certainly changed in the preceding approximately two decades, it nonetheless continued to impact these women's lives, showing little or no sign of abating. Investigating these developments for more than a decade, the research upon which this article is based provides ethnographic evidence of the persistence of gender inequality, documenting the disproportionate share of work or burden with which middle‐class women were shouldered. This burden came in three basic arenas: work outside the home, work inside the home, and sociocultural or symbolic work. Combined, these three pillars of inequality demonstrate that gender norms and expectations in Vietnam, while certainly not static, are best understood as a refashioned version of the longstanding imbalance between men and women in a society wherein healthy gender relations have remained at least partly illusive.